Desire, Despair and Delirium in the Selected Love Poems of Vikram Seth: Exploring the Depths of Love in Vikram Seth's Poetry (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The poetry of Vikram Seth has multiple layers of themes but his love poetry is entirely different in nature and treatment from his other themes. He does not present only the beautiful and romantic side of love like William Shakespeare, John Donne, and Robert Browning, rather he talks about the unsatisfied desires which lead him to despair and then it seems that he has lost his emotional balance in the life and become a victim of delirium. Love, being the basic desire of the universe, plays an important role in the life of every individual. The omnipresent and omnipotent love, is the cause of the growth of this universe and every living being of it. Desire of love ties us all together. Everything and everyone who has taken or takes and will take birth on this earth, is born without religion but not without love. But the study of this research is focused on love between lovers. The desire is the cause of every pain. When desire is not properly satisfied or fulfilled it causes despair, frustration, separation and delirium. In the final stage of delirium, nothing remains in the life of a lover except darkness, despair, sorrow and negativity. This disastrous effect of love has to be faced by a lover all alone. Even nature plays an important role in it. When lovers are happy with each-other the nature, even in the autumn season plays a vital and supporting role in their lives. But if the lovers are separated or rejected by each-other the nature, even in spring and rainy season fill their hearts with despair, negativity, glum and delirium. Inat this stage nothing remains good or positive for them.